A successful aggressive surgical and medical approach to pulmonary artery obstruction due to Mycobacterium abscessus infection post lung transplantation. Issue 2 (19th February 2018) - Kotecha, Sakhee; Smibert, Olivia C.; Doi, Atsuo; Gooi, Julian; Morrissey, Orla; Paraskeva, Miranda; Snell, Greg I.; McGiffin, David
Abstract: Mycobacterium abscessus infection following lung transplantation has historically been associated with poor outcomes. We report a case of bilateral lung retransplantation complicated by obstruction of the right pulmonary artery secondary to M. abscessus mycotic aneurysm. Aggressive surgical management, including reconstruction of the right pulmonary artery, was undertaken with prolonged antimicrobial therapy. Thirty‐six months later, antibiotics have been discontinued and the patient has stable soft tissue chest wall disease with good graft function. Mortality and morbidity associated with M. abscessus infection is considerable but this case illustrates that with aggressive early management, outcomes may be favorable.